Ornelas, Jorge; Cíntora, Armando (eds.). Dudas filosóficas. Ensayos sobre escepticismo antiguo, moderno y contemporáneo. (2015)
Ornelas, Jorge; Cíntora, Armando (eds.). Dudas filosóficas. Ensayos sobre escepticismo antiguo, moderno y contemporáneo. México, Barcelona: UAM-Gedisa, 2014. 424 pp.